Improved mechanical adhesion and electronic stability of organic solar cells with thermal ageing: the role of diffusion at the hole extraction interface. Issue 6 (23rd January 2017) - Greenbank, W.; Rolston, N.; Destouesse, E.; Wantz, G.; Hirsch, L.; Dauskardt, R.; Chambon, S.
Abstract : Organic photovoltaic solar cells are a promising option for cheap, renewable energy, but must improve in their stability. Abstract : Organic photovoltaic (OPV) solar cells are a promising option for cheap, renewable energy, but must improve in their stability. This study examines changes in the IV parameters of inverted OPV devices with thermal ageing and correlates them to changes in the mechanical stability of the devices observed by fracture analysis. In particular, the role that the use of different materials in the hole transport layer (HTL) and metal electrode has in determining the stability (both mechanical and electronic) of the device is studied. Data from a range of characterization techniques (including Kelvin probe analysis and X-ray photoelectron spectroscopy elemental depth profiling) are used to correlate changes in device structure and performance, demonstrating the presence of inter-layer diffusion when silver is used as an electrode material. This inter-diffusion has the beneficial effect of improving the adhesion of the electrode to the device, but is correlated to declines in the performance of the device when used in conjunction with MoO3 as an HTL. An improvement in adhesion is also seen with aluminium electrodes, but without any signs of diffusion, showing that an improvement in the mechanical stability of a device when thermally aged need not come at the expense of performance stability.